Public-private partnerships for skill development in the United States, Russia, and China - Remington, Thomas F.; Yang, Po (Post-Soviet Affairs, 2020)
We compare three countries where public policy has explicitly sought to align incentives of employers and educational institutions around closing the gap between skill formation and labor market demand. In large, heterogeneous countries such as the United States, Russia and China, collaborative arrangements such apprenticeships and other forms of public-private partnerships can be constructed at the subnational level by building on direct, face-to-face ties across educational, business, government, and civic sectors. Drawing on existing literature as well as fieldwork studying a number of specific cases in the three countries, the paper develops a typology of such arrangements and proposes an explanation for the observed variation. It emphasizes the importance of two sets of factors: those that induce cooperation on the part of firms and schools, and those that influence the character of such partnerships.